Default mode network activity and white matter integrity in healthy middle-aged ApoE4 carriers - Patel, K; Stevens, M; Pearlson, G; Winkler, A; Hawkins, K; Skudlarski, P; Bauer, L (Springer-Verlag, 2013)
Alzheimer’s disease (AD) is most commonly detected during old age, but the underlying neuropathologic changes likely appear decades earlier, especially among patients possessing genetic risk factors, such as the isoform E4 of the apolipoprotein E (ApoE4). In this study, we used magnetic resonance imaging (MRI) to assess default mode network (DMN) connectivity in 22 ApoE4 non-carriers and 14 matched ApoE4 carriers as well as white matter fractional anisotropy (FA) in 15 ApoE4 non-carriers and 11 demographically matched ApoE4 carriers. Cognitive tests were also administered. All of the participants were middle-aged adults. The analysis revealed no cognitive or white matter FA differences between carriers and non-carriers. However, in DMN regions previously implicated in AD, we did detect decreased functional connectivity. Our findings suggest that functional MRI abnormalities may be detectable well before cognitive decline or white matter changes among individuals at increased genetic risk for AD.